DESAIN PENELITIAN KURIKULUM DALAM PENGEMBANGAN ILMU KEPENDIDIKAN - sinaga, Reflina; Asnita Hasibuan; Candra Ronitua Gultom; Ester Julinda Simarmata; Fiber Yun Almanda Ginting; Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Curriculum research design is a methodological framework used to scientifically study, develop, implement, and evaluate curricula. In the development of educational science, curriculum research design serves as a means to generate new knowledge, whether in the form of theories, models, or curriculum practices that are relevant to the needs of students and educational contexts. Through appropriate research design, curriculum developers and educational researchers can deeply understand the relationship between objectives. This research uses a qualitative approach with a developmental orientation (developmental research), combined with Research and Development (R&D) and Design-Based Research (DBR) approaches.